A munkaoktatás kezdeti fázisai az értelmi fogyatékos gyermekek gyulai és kisújszállási gyógypedagógiai intézeteiben a 20. század közepéig - Gál, Anikó (Per Aspera ad Astra, 2015)
Our research aims to investigate how job training was carried out in the special education institutes of Gyula and (from 1928) Kisújszállás. We can conclude that at both institutions the educational and pedagogical work placed great emphasis on working with people with learning disabilities in order to prepare them for work, and to expand the job opportunities available to them, thus contributing to the promotion of social integration as well. They especially focused on preparing and conditioning students for work, bearing in mind that the workers should like the activities and should receive education appropriate for their abilities. The local conditions provided a great opportunity for practical employment and further development. (Translated by Ágnes Lengvári)